The Development of a Geographic Information System for Mapping Creative Economy Actors in Balikpapan Using the Prototype Method - Raihan Maheswara Rawanggalih; Asep Nurhuda; Bagus Satria (Politeknik Pertanian Negeri Samarinda, 2024)
Geographic Information Systems (GIS) play a crucial role in collecting, managing, analyzing, and presenting geographically referenced data. This research focuses on the development of a GIS-based application designed to map and analyze the distribution of creative economy participants in Balikpapan. Using the System Development Life Cycle (SDLC) Prototype method, the study integrates spatial data with geographic analysis, utilizing technologies such as Node.js, Leaflet, Laravel, and QGIS in the development process. Data related to creative economy actors is gathered locally, while spatial data is sourced from the Ina Geoportal website. This web-based application provides comprehensive mapping capabilities, enabling users to identify strategic business locations, optimize business potential, and improve service accessibility. Additionally, the tool aims to offer insights for local government policymaking, contributing to regional economic growth and enhancing community welfare. The integration of GIS into the application also supports the preservation and promotion of regional cultural identity, offering valuable information for sustainable development. Ultimately, this research highlights the significant role of GIS in improving economic planning, fostering informed decision-making, and driving sustainable development in Balikpapan.